Prepectoral implant placement in plastic-reconstructive breast surgery – a contribution to the discussion - Paepke, Stefan; Ohlinger, Ralf; Klein, Evelyn; Thill, Marc (Senologie - Zeitschrift für Mammadiagnostik und -therapie, 2018)
Implant-based breast reconstruction has gained a high and increasing level of importance both nationally and internationally in recent years and covers a wide spectrum of reconstruction techniques. The standard procedure in nipple-sparing subcutaneous mastectomies is currently performed by placing the implant into a subpectoral pocket beneath the pectoralis muscle. The use of implant-based reconstructive techniques with the need for internal support to reconstruct the inframammary fold, to cover the implant at the lower pole and to provide a stable but flexible implant position has become relevant and led to the introduction of heterologous materials such as acellular dermal matrices and synthetic meshes. Although the safety and aesthetics of this approach have produced good results, prepectoral techniques add a whole new dimension with the development of the next generation of acellular dermal matrices and, especially, titanised implant pockets created specifically for prepectoral implant placement 1 have brought about a renaissance in muscle-sparing reconstructive techniques. These preserve the natural anatomy, thereby avoiding the adverse effects associated with submuscular reconstruction, including preservation of full shoulder function, minimising postoperative pain and the risk of bleeding and haematoma, and animation deformities such as “jumping breast phenomenon”. A new method of implant-based breast reconstruction is therefore available and must be analysed regarding indications and benefits.
Keywords: implant-based breast reconstruction; synthetic meshes; titanised polypropylene mesh TiLoop®Bra and TiLoop®Bra-Pocket; prepectoral implant; implantatbasierte Brustrekonstruktion; Synthetische Netze; titanisierte Polypropylene-Netze TiLoop®Bra und Tiloop®Bra-Pocket; präpektorale Implantateinlage